Social media warfare equal weapons for all - Erbschloe, Michael (CRC Press, Taylor & Francis Group, 2017)
Social media applications can be weaponized with very little skill. Social media warfare has become a burden that nation states, government agencies, and corporations need to face. To address the social media warfare threat in a reasonable manner that reduces uncertainty requires dedication and attention over a very long-term. To stay secure, they need to develop the capability to defend against social media warfare attacks. Addressing unconventional warfare strategies and tactics takes time and experience, plus planning and dedication. This book will help managers develop a sound understanding of how social media warfare can impact their nation or their organization.